ESTIMATION OF EFFICIENCY UTILIZATION OF ELEMENT N BY SOYBEAN (Glycine max (L) merr.) USING SPAD METHOD DUE TO INCREASING DOSAGE OF BIODIVE FERTILIZER VP3 AND LONG ELECTRIC INDUCTION - Anggri Fri Agung; Djuhari Djuhari; Novi Arafita (AGRONISMA, 2021)
This study aims was to find out the estimated efficiency of the utilization of element N by soybean plants using the SPAD (Soil Plant Analysis Development) method due to increased doses of VP3 biological fertilizer and long induction of electricity. This research was conducted in the trial land of Griya Shanta, Brawijaya University, Malang and Microbiology Laboratory, Universits Islam Malang. The design used is a Simple Random Group (RAK) design with 13 treatments repeated 3 times. N uptake is calculated using the SPAD method. The results of this study showed that the application of VP3 bio-fertilizer supported by certain electrical inductions was able to compensate for the use of inorganic fertilizers and can increase the chlorophyll content shown at the best treatment, namely NL1 (NPK 100% + 30-minute electricity induction) but not real different from V2L1 treatment (VP3 200% + 30-minute electricity induction), V2L1 (VP3 200% + 30-minute induction),Â  V2L2 (VP3 200% bio fertilizer + 60-minute electricity induction), NL2 (NPK 100% + 60-minute electricity induction), V2L3 (VP3 200% bio fertilizer + 90-minute electricity induction), V1L1 (VP3 100% bio-fertilizer + 30-minute electricity induction), V1L2 (VP3 100% induction + 60-minute induction), While the highest treatment is V1L2 (100% VP3 bio fertilizer + 60 minutes induction) with a productivity of 5.46 Tons / ha.